Analysing the impact of funding gap on financial perfomance of smes: a case study of Best Bake Foods (pvt) ltd. - Shumba, Innocent (Midlands State University, 2017)
The objective of this study was to analyse the impact of funding gap on financial performance of SMEs in Zimbabwe focusing on Best Bake Foods (Pvt) Ltd as a case study within a period 2013-2015. The study was motivated by the deterioration of service provision, failure to pay outstanding bills and failing to maximise potential capacity which was caused by the funding gap. This has negatively impacted on the financial performance of the entity as shown in its financial statements. The research went on to review the previously related literature so as to identify views and opinions of other authors and the areas which lacks literature in relation to this subject. A combination of descriptive, correlation and explanatory research design with a mixed approach method and a sample of 65 respondents was used to collect both primary and secondary data using closed ended questionnaires and interviews. The research used charts, graphs and tables to present and analyse the data. From the research it was concluded that poor working capital management and limited access to normal credit facilities are the main causes of funding gap in SMEs and this gap has a negative impact on financial performance of SMEs. The recommendations include investing in working capital management, adopting financial bootstrapping methods, arrange business seminars and keeping of proper business records.